2016
DOI: 10.1097/cmr.0000000000000240
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral, antioxidant, and antimelanogenesis potencies of Hawthorn, a potential natural agent in the treatment of melanoma

Abstract: The lack of an efficient agent that does not have the disadvantage of low activity (kojic acid), high cytotoxicity, and mutagenicity (hydroquinone), poor skin penetration (arbutin), or low stability in formulation (glabridin) led us to continue our research on new antipigmentation/skin-lightening agents. Therefore, research of natural products that can modulate the metabolism of pigmentation is of great interest. Otherwise, malignant melanoma is one of the most aggressive forms of skin cancer, with high metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Extract-induced growth inhibitory effect in human colorectal cancer cell lines HCT-116 and HT-29 was associated with DNA fragmentation, sub-G1 peak, loss of mitochondrial potential, and poly (ADP-ribose) polymerase (PARP) cleavage. The extract also induced the cleavage of caspase-8 and had no effect on steady-state levels of total Bcl-2 protein, whereas Bax levels decreased significantly in a dose-dependent manner in both tested cell lines (Mustapha et al, 2016b). It may also be mentioned that in searching of relatively mild and safe tyrosinase inhibitors, one of six isolated from C. pinnatifida seeds 8-0-4′ neolignans, demonstrated promising tyrosinase-inhibiting and good antioxidant activities (Huang et al, 2015b).…”
Section: Venskutonismentioning
confidence: 89%
See 2 more Smart Citations
“…Extract-induced growth inhibitory effect in human colorectal cancer cell lines HCT-116 and HT-29 was associated with DNA fragmentation, sub-G1 peak, loss of mitochondrial potential, and poly (ADP-ribose) polymerase (PARP) cleavage. The extract also induced the cleavage of caspase-8 and had no effect on steady-state levels of total Bcl-2 protein, whereas Bax levels decreased significantly in a dose-dependent manner in both tested cell lines (Mustapha et al, 2016b). It may also be mentioned that in searching of relatively mild and safe tyrosinase inhibitors, one of six isolated from C. pinnatifida seeds 8-0-4′ neolignans, demonstrated promising tyrosinase-inhibiting and good antioxidant activities (Huang et al, 2015b).…”
Section: Venskutonismentioning
confidence: 89%
“…The studies performed by Mustapha et al (2015Mustapha et al ( , 2016a, c) demonstrated various effects of C. azarolus ethyl acetate extract as well as isolated from it hyperoside and vitexin-2″-O-rhamnoside. The extract and vitexin rhamnoside exhibited anti-proliferative activity against B16F10 melanoma cells and the ability to reduce melanin content by inhibiting the tyrosinase activities (Mustapha et al, 2015); it also demonstrated significant cellular antioxidant capacity against the ROS in B16F10 and primary human keratinocyte cells (Mustapha et al, 2016b). In addition, total oligomeric flavonoids extract (150 mg/kg body weight, 21 days) significantly inhibited tumor growth volume and weight in Balb/c mice inoculated with B16F10 cells and therefore was suggested as a new candidate for skin care products (Mustapha et al, 2016b).…”
Section: Venskutonismentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous natural products have been tested in efforts to discover novel anti-cancer therapeutic agents for the treatment of various tumors because natural agents typically exhibit fewer side effects than currently used anti-cancer chemotherapeutic drugs [ 14 , 15 ]. Nitidine chloride (NC), a natural benzophenanthridine alkaloid, is a major active compound present in a well-known traditional Chinese medicinal herb Zanthoxylum nitidum [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latter group inhibits melanin synthase to lighten hair and it is the reason that arbutin was widely used in the cosmetic hairdressing industry. Furthermore, recent reports have showed that arbutin exhibited many biological activities, including antioxidant, diuretic, antibacterial, anti-inflammatory, anti-tussive, anticancer and so on ( Mustapha et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%